Deficiencias en la entrevista médica: Un aspecto del método clínico - Miguel Moreno Rodríguez (Medisur)
To assess, under direct visualization, medical interviews, performed by 48 interns in 96 inpatients, we used a list of 44 deficiencies. Such deficiencies concerning to the history of the present disorder (HPD), types of questions, and general features, classified as mayor, important, and minor. There was a total of 783 deficiencies (media, 8.1 per interview) where 29.6 % corresponded to HPD, 20 % to types of questions, and 50,4 % to general features. 27 % were major, 46.4 % were important, and 26.6 % were minor. It was evident that there is a trend to obtaining information by means of brief and closed questions, inducing to responses and start by personal pathologic backgrounds, as well as serious difficulties in interrogation abilities. Some deficiencies must not arise so frequent in the last year of study. More than third of interns weren´t supervised just when they obtained data for medical record. We conclude that there is the need for increase direct supervision of students as a fundamental measure to improve their clinical abilities in making medical records.